New data on the ultrastructure of stomatocysts, plate and spines scales of Chrysosphaerella coronacircumspina (Chrysophyceae, Chromulinales) - Bessudova, Anna Yu.; Firsova, Alena D.; Likhoshway, Yelena V. (Acta Biologica Sibirica, 2024)
An updated and refined description of the ultrastructure of siliceous elements – plate and spine scales, as well as the morphotype of the stomatocyst Chrysosphaerella coronacircumspina is provided using scanning and transmission electron microscopy. A wide range of sizes of plate scales of C. coronacircumspina allows us to distinguish two types of them – large and small elliptical. Also, single small subcircular plate scales were discovered for the first time. The spine scales of C. coronacircumspina can grow up to 22.8 μm in length. The collar of the found morphotypes of stomatocysts has a smaller diameter (2.6 μm) than previously described. In the studied reservoirs, C. coronacircumspina cells were found mainly in the summer and autumn season, and stomatocysts only in autumn.